Propuesta de optimización de los procesos productivos en la empresa BOLANSHET. - Chóez Sánchez, Darío Alejandro (2019)
The current project is framed in improving the utility of the Bolanshet company by directing itself to its production processes such as aplanchado, orejitas, biscochos and quesadillas. Then the above-mentioned processes will be those that are subject to evaluation in order to obtain possible shortcomings and at the same time options that counteract these deficiencies to optimize both production and utility. These are analyzed through the results obtained from the study of methods or study of the work, accompanied by a production planning in inventories and labor, which leads to develop new indicators such as production capacity, raw material costs, hand costs of work, inherent costs in production, perceived utility for sales (Gross profit), utility for business turnaround (net profit) which helps to standardize production values. Once the different studies have been analyzed, four proposals are obtained, which will help to improve different problems in machinery, labor, spaces and workplaces, raw materials and productive processes that intervene in the elaboration of each product. These proposals will allow the company to observe the costs, as well as the benefits that each of them would have.